2016
DOI: 10.1108/ijpsm-02-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

The activating profession: coaching and coercing in the welfare services

Abstract: Anniken Hagelund2 Purpose: Activation policies are key elements of contemporary welfare reform throughout Europe. The paper aims to explore the consequences of more active and individualised welfare policies for conceptualisations of professionalism and competence in the welfare services.Design/methodology/apporach: The primary data are 25 qualitative interviews with streetlevel bureaucrats conducted in two local offices in The Norwegian Labour and Welfare Administration (NAV). These data were supplemented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 25 publications
2
24
0
8
Order By: Relevance
“…Thus, this dimension provides training courses, work skills, job counselling, psychosocial counselling and job inclusion assistance. Marchal and Van Mechelen (), in line with other observers (e.g., Dean, ), suggested that, like those of other Nordic countries, Norwegian activation frontline work is characterised by a relatively strong emphasis on the enabling dimension in terms of various skill‐enhancing activities (Hagelund, ), with inclusion in the labour market as the primary focus. Although activation work is mainly a mix of demanding and enabling elements (Aurich, ), the emphasis that is put on the enabling elements in the Norwegian context will plausibly have implications for service provision and frontline workers' attitudes and everyday practices.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Thus, this dimension provides training courses, work skills, job counselling, psychosocial counselling and job inclusion assistance. Marchal and Van Mechelen (), in line with other observers (e.g., Dean, ), suggested that, like those of other Nordic countries, Norwegian activation frontline work is characterised by a relatively strong emphasis on the enabling dimension in terms of various skill‐enhancing activities (Hagelund, ), with inclusion in the labour market as the primary focus. Although activation work is mainly a mix of demanding and enabling elements (Aurich, ), the emphasis that is put on the enabling elements in the Norwegian context will plausibly have implications for service provision and frontline workers' attitudes and everyday practices.…”
Section: Introductionmentioning
confidence: 79%
“…Several researchers have argued that user‐oriented competency is relatively safeguarded, and have simultaneously stressed the need for higher market competency among frontline workers in labour and welfare administration (e.g., Frøyland & Spjelkavik, ; Hagelund, ). The results of the present study support this view, considering that they scored themselves somewhat higher on the user‐oriented competency subscale than on the market competency subscale.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations